MACROSEISMIC AND MICROSEISMIC ANALYSIS OF M4.4 BATANG EARTHQUAKE, July 7, 2024 - Wibowo, Nugroho Budi (KURVATEK, 2024)
On July 7, 2024, an M4.4 earthquake affected Batang, Warungasem, and Wonotunggal sub-districts, causing minor to major damage to houses. This study intends to conduct macroseismic and microseismic studies in the earthquake-affected zone. Macroseismic analysis involves determining the amount of building damage on the MMI intensity scale, whereas microseismic analysis relies on dominant frequency characteristics (fo), amplification factor (Ao), and local geology. Macroseismic study indicates that the Batang earthquake had an intensity of III-IV MMI. The amount of light-to-heavy building damage does not affect the earthquake intensity (MMI) number. This is because the destroyed structures were constructed in a simplistic manner and were not earthquake-resistant. Microseismic investigation revealed that the Alluvium Plain had the dominating distribution of damage, with fo values <3.4 Hz and Ao >4.8. Aside from building quality, local geological variables have an impact on earthquakes on the surface.